Analisis Terhadap Terjadinya Tindak Pidana Perjudian Yang Dilakukan Oleh Anak Dibawah Umur - Bambang Hartono (PRANATA HUKUM, 2014)
Gambling is a form of social pathology. Gambling became a real or potential threat to the social norms that could threaten the ongoing social order, thus gambling can become an obstacle to national development beraspek material - spiritual. Therefore gambling should be addressed in a rational way. One such effort is the rational approach to criminal law enforcement policy. The problem faced is whether the policy in Indonesian criminal law that there has been sufficient time in order to overcome gambling and how the criminal law applicable policies. As well as how the criminal law policy formulation in the future to cope with gambling offenses. Criminal liability of children who commit gambling offenses punishable and punished as referred to in Article 303 bis paragraph (1) to - 2e of the Criminal Code, on the basis of these elements, then the defendant was sentenced to imprisonment for 2 (two) months in jail is in order be a deterrent against defendants accused of committing criminal offenses gambling. The process of criminal enforcement system against gambling offenses committed by minors, it can account for a criminal offense in the Criminal Code that is generally determined in a negative way, namely in terms of the penalty exceptions. The factors that lead to gambling offenses committed by minors are: law enforcement factors, environmental factors family itself, environmental factors or the community and lack of socialization of the Act prohibitions on gambling and there is a lack of understanding on existing Articles of the Criminal Code relating to gambling.